STRATEGIES ADAPTED TO CURB DEPRESSION IN MEDICAL AND ENGINEERING STUDENTS AND THEIR EFFICACY: A COMPARATIVE STUDY - Siddiqui, Naveed Ali; Tauseef Ahmed; Muhsin Ali; Syed Hasnain Ahmed; Muhammad Usama Roshan; Rahila Aman (Pakistan Journal of Physiology, 2024)
Background: The most common and serious psychiatric illness that negatively affects a person’s thoughts, and behaviour is depression. This study discusses the strategies that can be adapted to curb the depression between medical and engineering students of different medical and engineering colleges in Karachi, Pakistan. Methods: A comparative cross-sectional study was conducted at different medical and engineering colleges of Karachi. Sample size of 362 was calculated using SPSS-22. A close ended, self-administered, modified form of standardized questionnaire was used which comprised of two parts. First part had questions for the assessment of depression and second part was comprised of strategies practiced by students. Hamilton Depression Scale (HAM-D) was used in scoring the depression level in the study subjects. Results: In engineering and medical colleges 82.87% and 56.9% students were found depressed repeatedly. The results were significant. Out of all the strategies stated by Medical and Engineering the most effective Strategy adopted by students was listening to music which shows overall, 93 (25.8%) students listen music most of the time, 68 (18.8%) students listen to music often, 78 (21.6%) students listen to music sometime, 66 (18.3%) listen to music rarely and 57 (15.5%) listen to music almost never as a strategy to curb the depression. Conclusion: Depression reducing intervention needs to be encouraged in professional program and mentors for the effectual addressing and solving the problems is required in all professional programs. Pak J Physiol 2024;20(3):62–6, DOI: https://doi.org/10.69656/pjp.v20i3.1747